2017
DOI: 10.1556/004.2017.034
|View full text |Cite
|
Sign up to set email alerts
|

Association of the severity of lung lesions with carcass and meat quality in slaughter pigs

Abstract: The aim of this study was to determine the association of lung lesions with carcass and meat quality traits in slaughter pigs and to describe the main morphological features associated with lung lesions. Macroscopic lesions on the lungs were detected in 67.09% of a total of 79 pigs examined. Histopathological examination revealed that acute and chronic interstitial pneumonia represented the commonest changes, detected in 26.67% and 33.33% of the cases, respectively. Bronchopneumonia was found in 33.33% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 24 publications
2
19
3
Order By: Relevance
“…The percentage of lung lesions associated with App lesions in herds confi rms the importance of this pathogen as a causative agent. Chronic pleural lesions are commonly detected at the abattoir, since the resolution of pleural lesions associated with pleurisy can take 3 months or more, very often the process is not completed prior to slaughter [3,6,7].…”
Section: Actinobacillus Pleuropneumoniae (App)mentioning
confidence: 99%
See 3 more Smart Citations
“…The percentage of lung lesions associated with App lesions in herds confi rms the importance of this pathogen as a causative agent. Chronic pleural lesions are commonly detected at the abattoir, since the resolution of pleural lesions associated with pleurisy can take 3 months or more, very often the process is not completed prior to slaughter [3,6,7].…”
Section: Actinobacillus Pleuropneumoniae (App)mentioning
confidence: 99%
“…It is well recognized that, moving and mixing pigs of different origin increase the risks of pleuropneumonia [3,50]. The disease can also take on a chronic form where production losses are affected and pathological lesions at slaughter, such as adherence, pleurisy and lung abscesses are usually seen [6,44,51]. The bacterium is diffi cult to detect in live pigs due to the labor intensive sampling procedure, and secondly because outbreaks are impossible to predict and develop rapidly, so it is impossible to monitor the course of colonization and infection in animals [3,51].…”
Section: Actinobacillus Pleuropneumoniae (App)mentioning
confidence: 99%
See 2 more Smart Citations
“…Abattoir‐detected pathologies cause significant negative effects such as: (a) farm financial losses attributed to decreased average daily weight gain, growth rate and feed digestibility, high morbidity and mortality, and increased medication and veterinary expenses (Jäger et al, ; Sanchez‐Vazquez et al, ); (b), abattoir operator losses due to trimming and discarding of organs unfit for human consumption (Jäger et al, ; Sanchez‐Vazquez et al, ); and (c) lower carcass quality (Čobanović et al, ; Permentier et al, ). Despite the fact that numerous studies have revealed that pork quality is affected by many different factors, only a few papers have been published about the relationships between pneumonia, pleurisy (Dailidavičienė, Januškevičienė, Jukna, Pockevičius, & Kerzienė, ; Dailidavičienė, Januškevičienė, Zaborskienė, & Garmienė, ; Karabasil et al, ; Minkus, Schutte, von Mickwitz, & Beutling, ; Permentier et al, ), liver milk spots (Čobanović et al, ; Theodoropoulos, Deligeorgis, Fegeros, Papavasiliou, & Rogdakis, ) and pork quality.…”
Section: Introductionmentioning
confidence: 99%